1990
DOI: 10.1161/01.cir.82.1.274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flecainide and quinidine on human atrial action potentials. Role of rate-dependence and comparison with guinea pig, rabbit, and dog tissues.

Abstract: Flecainide and other class IC antiarrhythmic drugs are effective in the prevention and termination of atrial fibrillation, but the mechanism of this action is unknown. To gain insights into potential cellular mechanisms, we evaluated the response of human atrial action potentials to equimolar therapeutic concentrations of flecainide and quinidine and compared this response to that of guinea pig, rabbit, and dog atria. Both compounds reduced Vm, more as activation rate increased, but flecainide was more potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 54 publications
(21 reference statements)
8
62
0
Order By: Relevance
“…Positive use-dependent APD prolongation without sodium channel blockade would seem to be an ideal profile of antiarrhythmic drug action. 33,34 Ambasilide is considered a class III antiarrhythmic drug,19 a classification consistent with the significant increases in AERP and VERP and lack of change in atrial conduction velocity that we observed in the present experiments. Our results indicate that class III agents may exhibit different patterns of frequencydependent action on atrial refractoriness.…”
Section: Potential Implications Of Our Findingssupporting
confidence: 86%
“…Positive use-dependent APD prolongation without sodium channel blockade would seem to be an ideal profile of antiarrhythmic drug action. 33,34 Ambasilide is considered a class III antiarrhythmic drug,19 a classification consistent with the significant increases in AERP and VERP and lack of change in atrial conduction velocity that we observed in the present experiments. Our results indicate that class III agents may exhibit different patterns of frequencydependent action on atrial refractoriness.…”
Section: Potential Implications Of Our Findingssupporting
confidence: 86%
“…12C). Mean APD and maximum diastolic potentials were within the standard ranges for canine atrial APs established by Wang et al (33). Over the 35-min pacing interval, mean reductions of 10.3 and 12.8 ms were observed for APD 90 and APD 50 , respectively, with 79% and 75% of the change occurred dur- ing the initial 15 min.…”
Section: Experimental and Model Ap Transientssupporting
confidence: 74%
“…This can lead to arrhythmia with no class III activity when needed the most. Likewise, the class IC compound flecainide has been shown to lose its beneficial effect at low heart rates (Wang et al, 1990). In contrast, we observed that NS3623-induced shortening of the QT interval is rate-independent meaning that it does not display reverse-use dependence.…”
Section: Discussionmentioning
confidence: 53%